EVALUASI PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF SEBAGAI INSTRUMEN PENINGKATAN KUALITAS PROSES BELAJAR-MENGAJAR: TINJAUAN PUSTAKA - Fadlul Amdhi Yul; Niska Ramadani; Hasan Maksum; Waskito Waskito (STKIP Pesisir Selatan, 2026)
This study aims to comprehensively evaluate the effectiveness of interactive learning media as an instrument for improving the quality of the teaching and learning process, as well as to identify the determining factors of its successful implementation across various educational levels. The study employed a library research . A total of 15 reputable scientific journal articles published between 2021 and 2025 were systematically selected from Google Scholar and DOAJ databases. Data analysis was conducted using thematic synthesis techniques to inductively identify cross-study patterns of findings. The findings reveal that interactive learning media encompassing augmented reality, gamification, digital multimedia, and technology-based evaluation platforms consistently enhances students' learning motivation, conceptual understanding, active engagement, and academic achievement. Digital-based formative evaluation is proven to strengthen the quality of real-time feedback. Nevertheless, its effectiveness is substantially influenced by educators' digital literacy competence, technological infrastructure availability, and the alignment of instructional design with learning objectives.